2022
DOI: 10.14476/jomp.2022.47.4.198
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effect of Media Education in Patients with Temporomandibular Joint Disorders

Abstract: The first-line treatment of temporomandibular joint disorders (TMDs) should include self-management and education. Self-management techniques include moist heat application, stretching, diet control, and mandibular rest position adjustment. Although the effectiveness of video educational resources has been studied in multiple sectors, their application in TMD management has not yet been explored. This study seeks to assess how effective media education was at motivating TMD patients to self-management and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Furthermore, a Cochrane review 55 reported that the effectiveness of NSAIDs, benzodiazepines, anticonvulsants, and muscle relaxants in treating TMD was unclear. Based on these previous studies, 56 , 57 we selected PT (TENS) as the control intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a Cochrane review 55 reported that the effectiveness of NSAIDs, benzodiazepines, anticonvulsants, and muscle relaxants in treating TMD was unclear. Based on these previous studies, 56 , 57 we selected PT (TENS) as the control intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In the HIRA data, the diagnosis rate of TMDs has increased consistently every year since 2011, both for subjects under and over 20 years of age. Yang and Kim [27] also showed an increasing trend in the diagnosis rate of TMDs when analyzed using data from HIRA between 2003 and 2005. Firstly, advancements in medical technology may have enhanced the ability to detect and diagnose TMDs.…”
Section: 7%mentioning
confidence: 92%
“…In addition, the JBNU data allowed treatment trends to be examined with a diagnosis rate, which may be a new approach to TMD research in pediatric dentistry. Notably, non-insurance items such as orthodontic treatment were examined in the present study using JBNU data, unlike in the study by Yang et al[27] which used only HIRA data. In future studies, the overall trend of reversible and irreversible treatments as well as the detailed analysis of each treatment should be analyzed.…”
mentioning
confidence: 99%